The business of women : marriage, family, and entrepreneurship in British Columbia 1901-51 - Buddle, Melanie, 1971- (Vancouver : UBC Press, 2010)
"Buddle offers a unique and important contribution to Canadian history She seeks not only to incorporate women into the history of business but also to reconceptualize business history itself by asking new questions about gender, business, and the family. Business history needs to undergo a gender "revolution." This book will promote such rethinking of the field" "Throughout history, Western women have inhabited a conceptual space divorced from the world of business. But women have always engaged in business. Who were these women, and how were they able to justify their work of those women who embraced British Columbia's frontier ethos in the early twentieth century. In this detailed examination of case studies and quantitative sources, Buddle reveals that, contrary to expectation, the typical businesswoman was not unmarried or particularly rebelious but a woman reconciling her enterpreneurship with her identity as a wife, mother, or widow. This groundbreaking study not only incorporates women into the history of business, it challenges commonly held benefits about women, business and the marriage between the two."--BOOK JACKET.
Businesswomen in British Columbia -- The marriage of business and women : family status and entrepreneurship in British Columbia -- Careers for women : sex segregation in self-employment -- "They are quick, alert, clear-eyed business girls" : the Business and Professional Women's Clubs of British Columbia -- "You have to think like a man and act like a lady" : gender, class, and businesswomen -- Conclusion : "darkened by family obligations" : reflections on the business of women.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Businesswomen -- British Columbia -- History -- 20th century; Self-employed women -- British Columbia -- History -- 20th century; Businesswomen -- Family relationships -- British Columbia -- History -- 20th century; Self-employed women -- Family relationships -- British Columbia -- History -- 20th century; Women -- Employment -- British Columbia -- History -- 20th century; Electronic books